Determinants of business-to-consumer e- commerce adoption among sme retailers in Saudi Arabia - Altayyar, Raed Saud D (2022)
E-commerce has not been popularly and effectively adopted among Small and Mediumsized Enterprises (SMEs) in developing countries, particularly in Saudi Arabia. Of the country’s 34 million citizens, 32 million are Internet users, yet only 12 million use ecommerce platforms and online services. In 2019, Saudi’s percentage of online shoppers was 43%, far below that of developed countries like the USA (81%), the UK (82%), China (76.5%), and the United Arab Emirates or UAE (80%). Thus, compared with other countries, especially with other Gulf States like the UAE, business-to-consumer (B2C) e-commerce has not been effectively implemented in Saudi Arabia. SMEs are among the most significant agents of economic growth and development because they create jobs, support innovation, and increase exports. However, the literature shows that the use of e-commerce in Saudi Arabia’s SME sector is extremely low. Given that research on e-commerce adoption is limited among SMEs in developing countries, this study aimed to investigate the factors that influence B2C e-commerce adoption among SME retailers in Saudi Arabia. Prior studies have mainly focused on culture at the social-cultural and national level as well as political and religious characteristics, leaving gaps at the organizational level. There also appears to be limited analysis of organizational culture’s moderating role in the adoption of B2C e-commerce. In the attempt to fill these gaps, this study integrated technological, organizational, environmental, and individual factors from the e-commerce literature to develop a model of e-commerce adoption for SMEs in Saudi Arabia. The survey research design was employed to collect questionnaire data from a sample of 363 retail SME owners from three states in Saudi Arabia, namely Riyadh, Makkah, and the Eastern Province. Descriptive statistics and structural equation modeling using Smart-PLS 3.0 were utilized to analyze and interpret the data. The results showed that relative advantage, cost in technology, Internet capability, technology readiness, ii competitive pressure, owner innovativeness, and owner IT knowledge have a positive effect on e-commerce adoption among SMEs in Saudi Arabia. However, firm size as well as regulatory and legal environment demonstrated an insignificant effect on the B2C adoption of e-commerce among SME retailers in the Saudi context. Moreover, the moderation test revealed that organizational culture (flexible orientation) significantly moderates the effects of technological, organizational, and individual factors on ecommerce adoption among SME retailers, but not the effect of environmental factors on e-commerce adoption. Theoretically, the study extends the technology-organization-environment (TOE) model and innovation diffusion theory (IDT) by establishing organizational culture as a moderating variable. Practically, the findings aid SMEs in improving their e-commerce adoption through the identified factors. However, this study has several limitations. First, the data was cross-sectional, whereby the associations among the variables cannot be used to infer longitudinal processes. Second, the current findings are specific to the SME and Saudi Arabian contexts, which impacts generalizability. Future studies should test the present model in other Gulf States and developing countries to compare results. This can help scholars better predict the adoption of e-commerce and the variables affecting them, especially across various other cultures. Research in the future should also focus on large enterprises, since they are more technologically advanced than small enterprises.